1966
DOI: 10.1113/jphysiol.1966.sp007973
|View full text |Cite
|
Sign up to set email alerts
|

The respiratory response of the new‐born lamb to inhaled CO2 with and without accompanying hypoxia*

Abstract: and values for both were reduced with the acid-base disturbances seen in the first 10 days after birth. Evidence was given which suggested that the response of the new-born lamb to inhaled C02 was similar to that of man acclimatized to a P-02 of 70-75 mm Hg.5. In the lightly anaesthetized lamb, bilateral section of the sinus nerves caused a small reduction in the sensitivity to inhaled 5 % C02 in air, an increase in the respiratory lag and a reduction in the rate at which v increased.6. It was concluded that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…In preterm human infants and preterm primates the total CO2 slope decreased when the inspiratory 02 concentration was lowered Guthrie et al 1985) despite the positive C02-02 interaction at the peripheral chemoreceptor level that was found in preterm infants (Albersheim et al 1976). Purves (1966) showed that in the term newborn lamb the total CO2 slope increased as Pa 2 fell, as in our piglets. and Guthrie et al (1985) speculated that the negative interaction between 02 and CO2 in infants may be related to different changes in medullary blood flow induced by hypoxia and hypercapnia in the newborn compared to adults (Hernandez, Brennan, Vannucci & Bowman, 1978;Rosenberg, Jones, Traystman, Simmons & Molteni, 1982;Koehler, Jones & Traystman, 1982).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In preterm human infants and preterm primates the total CO2 slope decreased when the inspiratory 02 concentration was lowered Guthrie et al 1985) despite the positive C02-02 interaction at the peripheral chemoreceptor level that was found in preterm infants (Albersheim et al 1976). Purves (1966) showed that in the term newborn lamb the total CO2 slope increased as Pa 2 fell, as in our piglets. and Guthrie et al (1985) speculated that the negative interaction between 02 and CO2 in infants may be related to different changes in medullary blood flow induced by hypoxia and hypercapnia in the newborn compared to adults (Hernandez, Brennan, Vannucci & Bowman, 1978;Rosenberg, Jones, Traystman, Simmons & Molteni, 1982;Koehler, Jones & Traystman, 1982).…”
Section: Discussionmentioning
confidence: 76%
“…The secondary depression, however, was found to be central of origin (Lawson & Long, 1983;Darnall et al 1991). Purves (1966) observed in one lamb an appreciable depression of the C02 slope during severe hypoxia (Pa, o2 = 2 8 kPa). He considered this as an example of a probably central depression of respiration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using three-point measurements to define 1i-PET co2 slopes, we found alinearities, or points of inflexion, in six of eight response lines. Alinearities of this sort have been described (Dejours et al 1965;Purves, 1966), and may arise because the alveolar PCO2 is underestimated when the Vt is small. Under such circumstances, measurements made in air should be ignored; the slope is best measured between the two hypercapnic points (Dejours et al 1965;Purves, 1966).…”
Section: Steady-state Responsesmentioning
confidence: 99%
“…Alinearities of this sort have been described (Dejours et al 1965;Purves, 1966), and may arise because the alveolar PCO2 is underestimated when the Vt is small. Under such circumstances, measurements made in air should be ignored; the slope is best measured between the two hypercapnic points (Dejours et al 1965;Purves, 1966). This observation has practical importance: our results indicate that twopoint measurements of slope (using air and 4 % C02) would have significantly underestimated the ventilatory response in most tests, calling into question the reliability of results obtained in this manner.…”
Section: Steady-state Responsesmentioning
confidence: 99%